2019
DOI: 10.1016/j.esxm.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Marijuana Use Prior to Sex and Sexual Function in Women

Abstract: Introduction Scientific research on the effects of marijuana on sexual functioning in women, including libido, arousal, orgasm, and satisfaction, is limited. Aim To evaluate women’s perceptions of the effect of marijuana use before sexual activity. Methods A cross-sectional design, from March 2016–February 2017, within a single, academic, obstetrics and gynecology practice, was performed. Patients were given a questionnaire at their visit and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…The specific impact of cannabis use on female sexual function was examined by Lynn et al, who found that self-reported improvement in sex drive and orgasm was associated with cannabis use before sex. 18 Similar to previous human studies, cannabis users in our cohort reported increased sexual frequency compared to non-users.…”
Section: Cuaj -Original Researchsupporting
confidence: 91%
“…The specific impact of cannabis use on female sexual function was examined by Lynn et al, who found that self-reported improvement in sex drive and orgasm was associated with cannabis use before sex. 18 Similar to previous human studies, cannabis users in our cohort reported increased sexual frequency compared to non-users.…”
Section: Cuaj -Original Researchsupporting
confidence: 91%
“…Participants or their partners who were diagnosed with systemic diseases (n ¼ 23), mental disorders (n ¼ 12), sexually transmitted diseases (n ¼ 9), and other serious conditions that led to sexual dysfunction or were taking any drugs that altered sexual function (n ¼ 14, including alcohol abuse and drug use) were excluded. 4,5 Homosexual or bisexual individuals (n ¼ 7) and pregnant and lactating women (n ¼ 29) were also excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…This is in contrast to the present study that found orgasm to be improved in more frequent users, whereas pain during sexual activity was unaffected. In contrast, Lynn et al 10 surveyed 373 women (127 users of cannabis) and reported that frequent users had improved orgasms (OR: 2.10, 95% CI: 1.01–4.44). Other realms of sexual function, such as satisfaction, sex drive, lubrication, and dyspareunia, were not impacted by either use vs not or frequency of use.…”
Section: Discussionmentioning
confidence: 97%
“… 7 , 9 Prior studies have either examined sexual function using a mix of validated and non-validated instruments with varied results. 10 , 11 Although a few studies have found a positive dose-dependent effect on arousal and shown a positive effect with pleasure, these studies have been small and have not examined other domains of female sexual function such as lubrication, pain, and overall satisfaction. 12 Interestingly, a large Australian survey found that men who used cannabis were more likely to report impaired sexual function, whereas women cannabis users did not have higher rates of sexual dysfunction.…”
Section: Introductionmentioning
confidence: 99%